Cyclic RGD targeting cisplatin micelles for near-infrared imaging-guided chemotherapy. Issue 2 (23rd December 2015) - Guan, Xingang; Hu, Xiuli; Liu, Shi; Sun, Xin; Gai, Xiaodong
Abstract : Nowadays imaging-guided chemotherapy is of great importance for developing highly efficient nanomedicines for cancer therapy. Abstract : Nowadays imaging-guided chemotherapy is of great importance for developing highly efficient nanomedicines for cancer therapy. However, drug accumulation and release in vivo cannot be tracked in most studies due to the imaging moiety. In this study, near-infrared (NIR) dyes, cisplatin and dextran were used to prepare an imaging-guided chemotherapy drug with a cyclic peptide arginine-glycine-aspartic acid (RGD) targeting property for the treatment of breast cancer. Confocal laser scanning microscopy (CLSM) analysis indicated that the cisplatin-loaded micelles with cRGD decoration were quickly taken up by breast cancers cells in vitro according to the fluorescence of the NIR dye. More importantly, in vivo bioluminescence imaging analysis indicated that the drug-loaded micelles were preferentially distributed in the tumor regions of tumor-bearing mice. Furthermore, combining RGD targeting, in vivo imaging and therapeutic properties, this nanomedicine was suggested to have a good anti-tumor activity in vivo . Our study highlights the potential of combining active targeting and NIR fluorescence imaging in one drug delivery system for cancer diagnosis and therapy.